TEKNIK SPLIT BOLUS TERHADAP INFORMASI ANATOMIS PADA PEMERIKSAAN CT SCAN UROGRAFI - Amelia Rizqi Utami; Nanang Sulaksono; Sigit Wijokongko (JRI (Jurnal Radiografer Indonesia), 2022)
Background : The split bolus technique in CT Scan urography is an intravenous contrast media insertion technique by combining two phases, namely the nephrography phase and the excretory phase in one scan acquisition. In general, the CT Scan urography examination uses 3 phases, non-contrast phase, the nephrographic phase, and the excretory phase. In the role of the split bolus technique, the combination of two phases, namely the nephrographic and excretory phases. The purpose of this study was to explain the split bolus technique and the role of the split bolus technique on anatomical information in CT Scan urography. Methods : This type of descriptive research using a literature review approach. The keywords used are "Split-bolus", "CT Scan Urography". Articles were obtained based on inclusion and exclusion criteria and 7 relevant scientific articles were obtained and were used as literature sources. Data processing through article extraction. Result : The split bolus technique in CT Scan urography examination is a technique of intravenous contrast media that combines two nephrographic and excretory phases in one image acquisition with an average flow rate of 1.5 ml - 3 ml / s. This technique uses a non-ionic iodine contrast medium with a volume of 90 ml - 135 ml and a concentration of 300 mg/ml-370 mg/ml. The role of the split bolus technique on radiation dose and anatomical image information is due to the merging of the two phases in one scan which addresses the anatomy of the urinary system. In addition, the split bolus technique when combined with several reconstructions is able to increase contrast resolution and increase organ enhancement. In this technique, it is better to use the addition of a reconstruction algorithm such as 3D MIP, so that the anatomical image information obtained is more optimal.